Changes in the system of organization and financing of culture in Poland in the years 2001-2008; Zmiany w systemie organizacji i finansowania kultury w Polsce w latach 2001-2008 - Adam Suchecki (Comparative Economic Research. Central and Eastern Europe, 2010)
After the collapse of socialism the democratic structures of the Polish government and the society are still in the way of forming process. After the year 1989 till now Poland make some formal and crucial steps to change the administrating system, also in the field of cultural policy and art institutions. This article will show the major reforms and changes in public administration system in Poland according to changes in the sphere of culture in the years 2001-2009 and the final form of the culture finance system. The reason of this time horizon is, that before year 2001 the data have been incomplete according to the spatial regional reforms in the local administration systems. I will try to show the effects of changes, such as how new administration and local governments use culture as a part of economic capital of the regions and cities, I will show changes in public expenditures for culture and new possibilities and plans of financing this sphere in Poland. – – Po roku 1989 zostały w Polsce zostały przeprowadzone reformy systemu administracji. Zmiany te dotyczyły roẃniezṗolityki kulturalnej i organizacji kultury. Artykuł ukazuje głoẃne reformy i zmiany jakie zaszły w systemie administracji publicznej, a zwłaszcza w sferze kultury w latach 2001-2009 oraz ostateczny kształt organizacji i finansowania kultury w Polsce. Powodem przyjecia takiego horyzontu czasowego jest fakt, zė przed rokiem 2001 dane mogły bycńiekompletne z powodu reform systemu administracji lokalnej. W artykule tym podjeta została prob́a ukazania efektoẃ przeprowadzonych reform, analiza wydatkoẃ publicznych na kulture oraz przedstawione nowe perspektywy i mozl̇iwosći finansowania tej sfery w Polsce.
Keywords: 330